Stiripentol: A Novel Antiseizure Medication for the Management of Dravet Syndrome. Issue 11 (November 2019) - Buck, Marcia L.; Goodkin, Howard P.
Objective: To describe the pharmacology, efficacy, and safety of stiripentol in the treatment of refractory seizures in patients with Dravet syndrome.Data Sources: A search of the English language literature was conducted using PubMed and MEDLINE (1978 to April 2019) with the search terms stiripentol, Dravet syndrome, and refractory epilepsy . Other resources included article bibliographies, prescribing information, and relevant trials athttps://clinicaltrials.gov/ .Study Selection and Data Extraction: All phase 1, 2, or 3 trials; observational studies; and retrospective studies were analyzed.Data Synthesis : In controlled studies, stiripentol has been shown to reduce seizure frequency by 50% or more in 40% to 70% of patients with Dravet syndrome. Reductions in seizure duration and episodes of status epilepticus have also been documented. Common adverse effects include somnolence and anorexia. Stiripentol inhibits the metabolism of clobazam and valproate, often requiring dose adjustment.Relevance to Patient Care and Clinical Practice: Stiripentol, a direct allosteric modulator of GABAA receptors, offers a novel approach to treatment in patients with Dravet syndrome, both with and without pathogenic variants of the sodium channel α-1 subunit gene, and potentially other refractory seizures. Although available outside the United States for a decade, it was only recently approved by the Food and Drug Administration for patients 2 years of age and older with Dravet syndrome taking clobazam.Conclusions: Stiripentol is an effective adjunctive therapy for reducing the frequency and duration of refractory seizures in patients with Dravet syndrome. Its role in the treatment of other refractory epilepsies requires further study.